(untitled) (Semiárida, 2020)
The Pteridophytes of La Pampa province, Argentina. In this contribution the whole species and varieties of ferns and allied plants known for that province are listed. Its pteridophytic flora is represented by 8 genera (Adiantum, Azolla, Blechnum, Cheilanthes, Equisetum, Notholaena, Pellaea y Woodsia) with 12 species, 1 subspecie and 2 varieties. A general key, geographic distribution and the habitat of the taxa are given. The ferns are growing in three highlander places of that province: Lihuel Calel, Cerro de los Viejos and the faulted block of San Rafael. Also, the floristic affinities and the probable migratory itineraries, only in relation to the Pteridophytes, are discussed.